GeNeDis 2016 : computational biology and bioinformatics - Vlamos, Panayiotis (Springer, 2017)
"The 2nd World Congress on Geriatrics and Neurodegenerative Disease Research (GeNeDis 2016), focuses on recent advances in geriatrics and neurodegeneration, ranging from basic science to clinical and pharmaceutical developments and provides an international forum for the latest scientific discoveries, medical practices and care initiatives. Advanced information technologies are discussed concerning the various research, implementation and policy, as well as European and global issues in the funding of long-term care and medico-social policies regarding elderly people. This volume focuses on the sessions from the conference on computational biology and bioinformatics."--Publisher's description.
Keywords: Nervous system -- Degeneration -- Congresses.; Computational biology -- Congresses.; Bioinformatics -- Congresses.; elektronické knihy; electronic books